The whole chromosome-level genome provides resources and insights into the endangered fish Percocypris pingi evolution and conservation - Zhi He; Chunxia Li; Kuo Gao; Xubin Zheng; Xuanyu Wang; Huiling Wang; Qiqi Chen; Ziting Tang; Mingwang Zhang; Deying Yang; Taiming Yan (BMC Genomics)
Abstract Background Percocypris pingi (Tchang) was classified as Endangered on the Red List of China′s Vertebrates in 2015 and is widely distributed in the Upper Yangtze River. Although breeding and release into wild habitats have been performed for this commercially important fish in recent years, low genetic diversity has been found in wild populations. Genomic resources are strongly recommended before formulating and carrying out conservation strategies for P. pingi. Thus, there is an urgent need to conserve germplasm resources and improve the population diversity of P. pingi. To date, the whole genome of P. pingi has not been reported. Results In our study, we constructed the first chromosome-level genome of P. pingi by high-throughput chromosome conformation capture (Hi-C) technology and PacBio long-read sequencing. The assembled genome was 1.7 Gb in size, with an N50 of 17,692 bp and a GC content from circular consensus sequencing of 37.67%. The Hi-C results again demonstrated that P. pingi was tetraploid (n = 98), with the genome consisting of 24-type and 25-type chromosomes. Chr.19 of the 24-type chromosomes in P. pingi resulted from the fusion of chr.19 and chr.22 in zebrafish. The divergence times between 24-type and 25-type chromosomes was around 6.1 million years ago. A total of 25,198 and 25,291 protein-coding genes were obtained from the 24-type and 25-type chromosomes, respectively. The ploidy of P. pingi is an allotetraploid. A total of 8,741 genes of P. pingi were clustered into 4,378 gene families that were shared with 14 other species, and the P. pingi genome had 68 unique gene families. Phylogenetic analyses indicated that P. pingi was most closely related to Schizothorax oconnori, and the genes were clustered on one branch. We identified 166 significantly expanded gene families and 173 significantly contracted gene families in P. pingi. The most enriched positive protein-coding genes, such as Bmp-4, Etfdh, homeobox protein HB9, and ATG3, were screened. Conclusion Our study provides a high-quality chromosome-anchored reference genome for P. pingi and provides sufficient information on the chromosomes, which will lead to valuable resources for genetic, genomic, and biological studies of P. pingi and for improving the genetic diversity, population size, and scientific conservation of endangered fish and other key cyprinid species in aquaculture.